Power, Property and Rural Agency in the Northwest of Iberian Peninsula between the end of the Roman Empire and the Feudal Consolidation (5th-12th centuries) - Escudero Manzano, Gonzalo J. (Huarte de San Juan. Geografía e Historia, 2026)
This dossier reviews the applicability of the historiographical concept of «no man’s land» in Early Medieval Spain. Through five contributions, it addresses various issues relating to the exercise of power by local societies, their relationships with supralocal powers, and the management of their territorial properties before the consolidation of feudal structures of domination. The joint conclusions reveal that Iberian Early Middle Ages were characterised by various local particularities, highlighting the adaptability of local societies in the face of interference from supralocal powers